A comparative study of phenolic compounds profile and in vitro antioxidant activity from buriti (Mauritia flexuosa) by-products extracts. (October 2021) - Rudke, Adenilson Renato; Andrade, Kátia Suzana; Mazzutti, Simone; Zielinski, Acácio Antônio Ferreira; Alves, Victor Rodrigues; Vitali, Luciano; Ferreira, Sandra Regina Salvador
Abstract: In general, buriti seeds (BSE) and buriti shells (BSH) are discarded or used as animal feed. However, these materials may have other destinations. Therefore, the aim of this work was to obtain extracts from BSE and BSH using different extraction techniques and solvents in order to evaluate their effects on phenolic profile and antioxidant capacity of the recovered extracts. Global yield, total phenolic content (TPC), in vitro antioxidant activities, and phenolic composition accessed by LC-ESI-MS/MS were evaluated. Principal component analysis (PCA) was used as a tool to correlate the observed data. Raw material, solvent type, and extraction method influenced the obtained results mainly in relation to the phenolic composition. BSH showed higher values of global yield, antioxidant activity, and TPC, compared to BSE. Considering the 46 phenolic compounds analyzed, 28 were quantified from BSE and 33 from BSH samples. Protocatechuic acid was the major phenolic compound found in most samples, except for the BSH extract obtained with pressurized liquid extraction (PLE), which presented quercetin as the main phenolic compound. PCA analysis demonstrated that flavonoids are most associated with the BSH, while phenolic acids and phenolic aldehydes are most related to BSE samples. Highlights: Phenolic composition of BSE was described for the first time. BSE had higher correlation with phenolic acids and phenolics aldehydes than BSH. Antioxidant activity for the extracts were higher for BSH than for BSE as biomass. 46 phenolics were monitored by LC-ESI-MS/MS, of which 28 from BSE and 33 for BSH.